ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN DAERAH - Gusrya Indah Sari; Fadli Fadli (Jurnal Akuntansi, 2017)
Respondents in this study are The Chief of Regional Work Unit, Chief of Financial Officer and Financial Officer of Regional Work Unit Bengkulu Province. The analysis method used SmartPLS 1.0 M3 program. The results showed that the implementation of good governance did not affect the quality of financial statement, the implementation of Government Accounting Standards has a positive effect on the quality of financial statements, and utilization of financial accounting information systems has a positive effect on the quality of financial statement.Keywords: Quality of Financial Statements, Good Governance, Government Accounting Standards, Regional Financial Accounting Information Systems